Intestinal microbiota: A promising therapeutic target for hypertension - Sun, Dating; Xiang, Hui; Yan, Jiangtao; He, Liqun (Frontiers in Cardiovascular Medicine, 2022)
Hypertension has developed into an escalating serious global public health problem with multiple and unclear pathophysiological mechanisms. Recent studies have identified the intestinal microbiota as a key perpetrator for hypertension through a variety of mechanisms. In this review, we highlight the potential roles of the intestinal microbiota and its metabolites in the development of hypertension, as well as the therapeutic potential for targeting the intestinal microbiomes. We also shed light on the main limitations and challenges of the current research and suggest the directions for future investigations. Finally, we discuss the development of accurate and personalized preventive and therapeutic strategies for hypotension by the modulation of intestinal microbes and metabolites.